2010
DOI: 10.1021/ol101173w
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of the Selective PI3 Kinase Inhibitor Liphagal

Abstract: The enantioselective total synthesis of liphagal, a selective inhibitor of PI3K α isolated from the marine sponge Aka coralliphaga, has been achieved. The novel tetracyclic "liphagane" skeleton is formed in one step, after the hydrogenation of a dihydroxydrimane phenol benzyl ether in the presence of cationic resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…VII → 1, pathway B in Scheme 1) by the Andersen, 6,15 Mehta, 13 Kumar, 14 and Ferreira 19 groups; ii) biomimetic ring expansion (pinacol-type rearrangement) approach (cf. IIIb → IVb, pathway A in Scheme 1) by the George, 11,12 Alvarez-Manzaneda, 16 and our 18 groups; and iii) nonbiomimetic approach (cf. Scheme 27) by the Stoltz group.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…VII → 1, pathway B in Scheme 1) by the Andersen, 6,15 Mehta, 13 Kumar, 14 and Ferreira 19 groups; ii) biomimetic ring expansion (pinacol-type rearrangement) approach (cf. IIIb → IVb, pathway A in Scheme 1) by the George, 11,12 Alvarez-Manzaneda, 16 and our 18 groups; and iii) nonbiomimetic approach (cf. Scheme 27) by the Stoltz group.…”
Section: Resultsmentioning
confidence: 89%
“…2a → 1 in Scheme 36), appears to be the most elegant methodology for the synthesis of the natural product. Relative to the enantioselective syntheses, the main advantage of our method is the higher overall yield [our synthesis (2014): 29.7% overall yield in 13 steps; 18 Andersen's synthesis (2010): 1.2% overall yield in 16 steps; 15 George's syntheses (2010, 2015): 9.2% overall yield in 13 steps, 12 4.6% overall yield in 11 steps; 11 Alvarez-Manzaneda's synthesis (2010): 15.9% overall yield in 12 steps; 16 Stoltz's synthesis (2011): 0.36% overall yield in 19 steps 17 ]. These syntheses are promising for the preparation of additional analogs of 1 in enantiomerically pure forms with the aim of exploring their structure-activity relationships, which will be useful for the design and development of novel therapeutic agents that target the inhibition of PI3Kα.…”
Section: Resultsmentioning
confidence: 94%
“…90 It has attracted interest as a PI3K inhibitor because, like many of the synthetic inhibitors discussed above it is more potent than LY294002 and more selective than wortmannin and it has an unusual structure. Recently, an enantioselective total synthesis of Liphagal has been reported 91 as well as the synthesis of a number of analogs. 92 …”
Section: Liphagal and Analogsmentioning
confidence: 99%
“…Numerous efforts have been devoted to the total synthesis of this class of natural products, [11] and there have been five reports on the total synthesis of 1. At almost the same time, George et al [10] and Alvarez-Manzaneda et al [13] reported the enantioselective total synthesis of naturally occurring (+)-1, which established the absolute configuration of 1 (Scheme 4). In this reaction, unfortunately, cyclized product 6 was formed as a 1:2.5 mixture of C8 epimers in favor of the undesired β-methyl isomer.…”
Section: Introductionmentioning
confidence: 95%